Implications of Good Aquaculture Practice (GAP) Application on Intensive Shrimp Ponds and The Effect on Water Quality Parameter Compatibility - Heri Ariadi; Tholibah Mujtahidah; Abdul Wafi (Journal of Aquaculture and Fish Health, 2023)
The purpose of this study was to evaluate the suitability of water quality parameters in intensive white shrimp (Litopenaeus vannamei) cultivation activities based on Good Aquaculture Practice (GAP) quality standards implication practice. This research was carried out with the ex-pose facto causal design concept during one cycle of shrimp cultivation, with the indicator being studied was the condition of the water quality parameters which were then corrected with the GAP standard according to the Minister of Agriculture Regulation No. 75 of 2016. The results showed that the condition of the water quality parameters during the cultivation period was still in accordance with the GAP quality standards, except for the alkalinity parameter which had a value of 157 mg/L and organic matter 104.43 mg/L, both values ​​were above the GAP quality standard threshold. The abnormal condition of the two parameters was caused by unpredictable natural and seasonal factors. This can be seen from the trend of the temperature and salinity parameter graphs that fluctuate unstable. Furthermore, for technical parameters, the cultivation system at the research site was still in accordance with the cultivation quality standards listed in the GAP. Based on the discussions, it can be concluded that the water quality parameters at the research pond location as a whole were still in accordance with the GAP quality standard which refers to the Minister of Fisheries Regulation No. 75 of 2016, except for the alkalinity and organic matter parameters which had a slightly worse concentration than the GAP quality standard.